1995
DOI: 10.1007/bf00866719
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of infections in Indian children with nephrotic syndrome

Abstract: We conducted a retrospective analysis of infections in 154 children (114 boys, 40 girls) with nephrotic syndrome who satisfied the International Study of Kidney Disease in Children criteria. Their mean age at onset of symptoms was 6.2 years (range 6 months to 16 years) and the mean duration of follow-up was 32 months (range 6-55 months). One or more infectious complications were observed in 59 of the 154 children (38%), with urinary tract infection being the commonest (13.7%), followed by pulmonary tuberculosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
6
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 10 publications
6
83
6
1
Order By: Relevance
“…In two studies abroad, it was 0.64% & 0.6% 1,6 . This might be due to small sample size in our study.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In two studies abroad, it was 0.64% & 0.6% 1,6 . This might be due to small sample size in our study.…”
Section: Discussionmentioning
confidence: 97%
“…We found only one case of Tuberculosis. But two Indian studies found it as 2 nd & 4 th most common infection (10.4% & 5% respectively) 6,10 . This difference might be due to the fact that all cases were not screened for tuberculosis and high success rate of immunization in Bangladesh might influence the result.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations